Combined Differential scanning calorimetry, Raman and Brillouin spectroscopies: A multiscale approach for materials investigation - Veber, Alexander; Cicconi, Maria Rita; Reinfelder, Heike; de Ligny, Dominique (Analytica Chimica Acta, 2018)
A new experimental setup combining DSC, Raman and Brillouin spectroscopies was developed. In order to estimate its accuracy and stability a study of silicon and the alpha-beta quartz phase transition were performed. The data obtained demonstrated good agreement with previous studies using these three different techniques. For quartz, the temperature behavior of its 147 cm(-1) Raman mode was studied in detail. Using a two-phonon coupling treatment of the Raman band, we show for the first time that its behavior can be well described by Landau theory of first-order phase transitions. The combined DSC-Raman-Brillouin technique is a powerful tool for material science capable of studying thermal, structural and elastic properties simultaneously. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Raman spectroscopy; Brillouin spectroscopy; Calorimetry; Quartz; Phase transition

Processing and characterization of aligned electrospun gelatin/polycaprolactone nanofiber mats incorporating borate glass (13-93B3) microparticles - Ege, Duygu; Pourshahrestani, Sara; Iorio, Francesco; Reinfelder, Heike; de Ligny, Dominique; Boccaccini, Aldo R. (Biomedical Materials (Bristol), 2023)
Aligned biodegradable fibers incorporating bioactive glass particles are being highly investigated for tissue engineering applications. In this study, 5, 7 and 10 wt% melt-derived 1393B3 borate glass (BG) microparticles (average size: 3.15 µm) were incorporated in 83 wt% polycaprolactone (PCL) and 17 wt% gelatin (GEL) (83PCL/17GEL) solutions to produce aligned electrospun composite nanofiber mats. Addition of 5 wt% BG particles significantly increased the alignment of the nanofibers. However, further incorporation of BG particles led to reduced degree of alignment, likely due to an increase of viscosity. Mechanical tests indicated a tensile modulus and tensile strength of approximately 51 MPa and 3.4 MPa, respectively, for 5 wt% addition of 1393B3 BG microparticles, values considered suitable for soft tissue engineering applications. However, with the increasing amount of 1393B3 BG, the nanofiber mats became brittle. Contact angle was reduced after the addition of 5 wt% of 1393B3 BG particles from∼45° to∼39°. Cell culture studies with normal human dermal fibroblast (NHDF) cells indicated that 5 wt% 1393B3 BG incorporated nanofiber mats were cytocompatible whereas higher doping with 1393B3 BGs reduced biocompatibility. Overall, 5 wt% 1393B3 BG doped PCL/GEL nanofiber mats were aligned with high biocompatibility exhibiting desirable mechanical properties for soft tissue engineering, which indicates their potential for applications requiring aligned nanofibers, such as peripheral neural regeneration.
CRIS-Team Scopus Importer:2023-09-08
Keywords: bioactive glasses; borate glasses; electrospinning; nanofiber; peripheral nerve tissue regeneration; soft tissue engineering